An open randomized controlled trial of the effects of linguistic simplification and mediation on the comprehension of "easy read" text by people with intellectual disabilities. Issue 2 (25th October 2019) - Buell, Susan; Langdon, Peter E.; Pounds, Gabrina; Bunning, Karen
Abstract: Background: This trial aimed to measure the effects of extrinsic and intrinsic factors on users' comprehension of health information provided in adapted written "easy read" material. Method: Sixty adults with intellectual disabilities undertook The Easy Read Task, randomly allocated with stratification by reading ability to one of four conditions (with and without simplified language/with and without mediation). Results: Neither linguistic complexity of the text nor mediation independently or combined made a significant difference to the understanding of information. Post hoc testing revealed that the group who received simplified language with mediation performed significantly better than the group that had complex text with mediation. None of the other differences between the remaining groups were significant. Conclusions: Constructing meaning needs to extend beyond a consideration of form as found in "easy read" documents to recognize the role of individual capacity for language processing.